Reflexiones acerca de México y la seguridad humana en el contexto de la cooperación internacional para el desarrollo - Villanueva Ulfgard, Rebecka (Revista Española de Desarrollo y Cooperación, 2023)
Mexico as international cooperation partner has the vocation to act both at the regional and global level in defense of human security, emphasizing the framework of the United Nations and the European Union. However, at the regional and national level Mexico faces important challenges to that vocation, especially in regard to the human security of undocumented migrants.